The employability of ex-offenders: A field experiment in the Swedish labor market - Ali M. Ahmed; Elisabeth Lång (IZA Journal of Labor Policy, 2017)
This paper presents the findings of a field experiment on hiring discrimination against ex-offenders in the Swedish labor market. Matched pairs of written job applications for fictitious male and female applicants with and without a past conviction of assault were sent to employers for nine different occupations. Results show that discrimination against ex-offenders exists, but the extent of it varies across occupations. The past conviction of assault was associated with 7-18 percentage point lower probability of receiving a positive employer response. Discrimination against ex-offenders was pronounced in female-dominated and high-skilled occupations. The magnitude of discrimination against ex-offenders did not vary by applicants' sex.
Keywords: C93; J71; K42; 330; Ex-offenders; Field experiments; Labor market discrimination